2019
DOI: 10.1186/s12862-019-1444-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved phylogenomic sampling of free-living nematodes enhances resolution of higher-level nematode phylogeny

Abstract: Background Nematodes are among the most diverse and abundant metazoans on Earth, but research on them has been biased toward parasitic taxa and model organisms. Free-living nematodes, particularly from the clades Enoplia and Dorylaimia, have been underrepresented in genome-scale phylogenetic analyses to date, leading to poor resolution of deep relationships within the phylum. Results We supplemented publicly available data by sequencing transcriptomes of nine free-livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
124
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(152 citation statements)
references
References 95 publications
22
124
0
Order By: Relevance
“…Secondly, mitochondrial 12S rRNA showed that there was a close relationship between clades IV and V, which has also been found in studies using the 18S rRNA gene and the transcriptome [7,11,12,31]. However, compared to phylogenetic studies using whole mitochondrial genomes, clade V was more closely related to Ascaridida, whereas clade IV was a sister clade to the clade consisting of clade V and Ascaridida [8][9][10].…”
Section: Potential Utility Of Mitochondrial 12s Rrna Gene In Nematodesupporting
confidence: 61%
“…Secondly, mitochondrial 12S rRNA showed that there was a close relationship between clades IV and V, which has also been found in studies using the 18S rRNA gene and the transcriptome [7,11,12,31]. However, compared to phylogenetic studies using whole mitochondrial genomes, clade V was more closely related to Ascaridida, whereas clade IV was a sister clade to the clade consisting of clade V and Ascaridida [8][9][10].…”
Section: Potential Utility Of Mitochondrial 12s Rrna Gene In Nematodesupporting
confidence: 61%
“…Publicly available protein sequences from complete genomes and assembled transcriptomes were downloaded when available. Dataset assembly and processing built on our established and routinely used bioinformatic pipeline 30,[64][65][66][67] with a number of modifications to help reduce possible exogenous contamination and low quality data (e.g., incorrectly translated gene predictions from Genescan; see below). Unassembled publicly available transcriptome data were digitally normalized and assembled using Trinity 68 .…”
Section: Molecular Laboratory Work One Specimen Of Laevipilina Antarmentioning
confidence: 99%
“…5 0 and 3 0 sequences terminal to the enzymatic domains were excluded. Under a general timereversible (GTR) model, designating Loa loa as outgroup a priori [38,39], and setting the number of rate categories that maximized the likelihood of the tree a posteriori, we performed 200 independent inferences from each matrix, with node support on the final trees estimated from 1000 bootstrap pseudoreplicates. In a second approach, we performed Bayesian inference from DNA sequences of enzymatic domains, including third codon positions, and specifying a codon model of substitution, as implemented in MRBAYES v. 3.2.6 [40].…”
Section: (B) Reconstruction Of Switch-gene Historiesmentioning
confidence: 99%